2005
DOI: 10.2174/156800705774322058
|View full text |Cite
|
Sign up to set email alerts
|

CREB, Synapses and Memory Disorders: Past Progress and Future Challenges

Abstract: In neurons, appropriate long-term adaptive responses to changes in the environment require the conversion of extracellular stimuli into discrete intracellular signals. Many of these signals involve the regulation of gene expression. The cAMP responsive element binding protein (CREB) is a nuclear transcription factor that modulates transcription of genes containing cAMP responsive elements (CRE sites) in their promoters. CREB is a key part of many intracellular signaling events that critically regulate many neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 210 publications
(323 reference statements)
4
114
0
1
Order By: Relevance
“…The factor plays an essential role in Aplysia long-term facilitation (Dash et al, 1990) and is reported to be important for the maintenance of LTP (Barco et al, 2002). As expected from these physiological results, several studies have documented a role for CREB in long-term memory in Drosophila and mice (Josselyn and Nguyen, 2005). These results suggest that increasing CREB activity would both facilitate LTP and the memory arising from it.…”
Section: Induction and Consolidationmentioning
confidence: 73%
See 1 more Smart Citation
“…The factor plays an essential role in Aplysia long-term facilitation (Dash et al, 1990) and is reported to be important for the maintenance of LTP (Barco et al, 2002). As expected from these physiological results, several studies have documented a role for CREB in long-term memory in Drosophila and mice (Josselyn and Nguyen, 2005). These results suggest that increasing CREB activity would both facilitate LTP and the memory arising from it.…”
Section: Induction and Consolidationmentioning
confidence: 73%
“…Efforts to promote consolidation have largely dealt with the late, protein synthesisdependent period (rather than the cytoskeletal assembly phase) and, in particular, on the cAMP responsive element binding protein (CREB) family of transcription factors (Lynch, 2002;Josselyn and Nguyen, 2005). CREB, after having been phosphorylated (and activated) binds to the cyclic AMP response element of target genes.…”
Section: Induction and Consolidationmentioning
confidence: 99%
“…It is unknown if the increase in p38 MAPK observed in our studies played a role in the CCL2-induced increase in synaptic network activity. Both p38 MAPK and CREB have been shown to play a key regulatory role in synaptic transmission, synaptic plasticity and memory mechanisms (Alonso et al, 2003;Brust et al, 2006;Butler et al, 2004;Josselyn and Nguyen, 2005;Rossato et al, 2006;Wang et al, 2007). Thus, these hippocampal synaptic functions may be an important target of CCL2 in the normal brain or during conditions associated with neuroinflammation and p38 MAPK may play a central role in the effects of CCL2 on these functions.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 and its primary receptor CCR2 are also widely expressed within the central nervous system (CNS), implicating roles for CCL2 in the CNS as well as in the immune system (Ambrosini and Aloisi, 2004;Bajetto et al, 2002). Sources of CCL2 within the CNS include microglia and astrocytes, although some neurons can also produce CCL2 (Babcock et al, 2003;Banisadr et al, 2005a;Farina et al, 2007;Josselyn and Nguyen, 2005;Kielian et al., 2002;Weiss and Berman, 1998) Emerging evidence supports both physiological and pathological roles for CCL2 in the CNS. CCL2 expression in the normal CNS starts at an early stage of development, suggesting a physiological role for CCL2 in CNS development (Geppert, 2003;Meng et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specific stressors in adult life have been reported to regulate hippocampal CREB expression (Alfonso et al, 2006;Song et al, 2006) and a decline in CREB expression has been observed in depressed patients (Blendy, 2006;Lai et al, 2003;Yamada et al, 2003). Besides its role in the regulation of BDNF, CREB has been shown to influence both structural and synaptic plasticity in the hippocampus (Josselyn and Nguyen, 2005;Nakagawa et al, 2002). Given the crucial role that BDNF and its upstream transcriptional activator CREB have been suggested to play in stress-related hippocampal damage (Blendy, 2006;Duman, 2004), understanding their regulation by distinct stressors in postnatal and adult life is critical.…”
Section: Introductionmentioning
confidence: 99%